Impact of disease management practices on finger millet blast and grain yield - P. DEVARAJE GOWDA, SAVITA EKKA and M.V.C. GOWDA, A. NAGARAJA*, BIJENDRA KUMAR T. RAGUCHANDER, A.K. HOTA, T.S.S.K.PATRO (Indian Phytopathology, 2012)
Finger millet [Eleusine coracana (L.) Gaertn.] is widely cultivated in India extending from Tamil Nadu in the South to Uttarakhand in the North with Karnataka having the highest area of about 1.0 m. ha (60% of the total). The crop doesn’t suffer much from diseases yet blast is a major production constraint at times causing heavy yield losses both in quality and quantity. Field experiment conducted during kharif 2008 and 2009 at eight locations with ten treatments for evaluating the performance of the recommended blast management practices revealed that, the disease pressure was high at all the centers except Bengaluru and Berhampur. Treatments involving resistant variety had less neck and finger blast disease compared to those with susceptible variety. Among the different treatments, seed treatment to resistant variety with either Carbendazim @ 2 gkg-1 or Pseudomonas flourescens 6gkg-1 reduced blast disease incidence by two and a half times over control besides recording high mean yield of 25.67 and 24.98 qha-1 as against 21.06 q in susceptible variety. Use of resistant variety itself had resulted in yield advantage of 2.23 qha-1. Hence instead of trying different chemical sprays for controlling blast on a susceptible variety, it is worthwhile to select resistant variety and give simple seed treatment with Carbendazim @ 2 gkg-1 or Pf @6 gkg-1.